Genome-wide meta-analysis identifies eight new susceptibility loci for cutaneous squamous cell carcinoma - Kavita Y. Sarin (Nature Portfolio, 2020)
The authors perform a meta-analysis of cutaneous squamous cell carcinoma, identifying causal variants within skin-specific regulatory elements.